It Is the Time to Think About a Treat-to-Target Strategy for Knee Osteoarthritis - Migliore A; Gigliucci G; Petrella RJ; Bannuru RR; Chevalier X; Maheu E; Raman R; Herrero-Beaumont G; Isailovic N; Matucci Cerinc M (Therapeutics and Clinical Risk Management, 2019)
A Migliore,1 G Gigliucci,1 RJ Petrella,2 RR Bannuru,3 X Chevalier,4 E Maheu,5 R Raman,6 G Herrero-Beaumont,7 N Isailovic,8 M Matucci Cerinc9 1Rheumatology Unit, San Pietro Fatebenefratelli Hospital, Rome, Italy; 2Department of Family Medicine, School of Kinesiology Western University, Western Centre for Public Health & Family, London, Ontario, Canada; 3Center for Treatment Comparison and Integrative Analysis Division of Rheumatology, Tufts Medical Center, Boston, MA, USA; 4Department of Rheumatology, Hôpital Henri Mondor, Creteil, France; 5Rheumatology Department, AP-HP, Saint-Antoine Hospital, Paris, France; 6Academic Department of Orthopaedics, Hull and East Yorkshire NHS Trust, Castle Hill Hospital, Cottingham, UK; 7Joint and Bone Research Unit, IIS-Fundacion Jimenez Diaz UAM, Madrid, Spain; 8Division of Rheumatology and Clinical Immunology, Humanitas Research Hospital, Rozzano, Milan, Italy; 9Division of Rheumatology AOUC, Department of Experimental and Clinical Medicine, University of Florence, Florence, ItalyCorrespondence: N IsailovicDivision of Rheumatology and Clinical Immunology, Humanitas Research Hospital, Via A. Manzoni 56, Rozzano 20089, Milan, ItalyTel +39-02-8224-5118Email natasa.isailovic@humanitasresearch.itAbstract: Osteoarthritis (OA) is a rheumatic disease that affects the well-being of the patient, compromises physical and mental function, and affects other quality of life aspects. In the literature, several evidence-based guidelines and recommendations for the management of knee osteoarthritis (KOA) are available. These recommendations list the different therapeutic options rather than addressing a hierarchy between the treatments and defining the real target. Therefore, a question arises: are patients and physicians satisfied with the current management of KOA? Actually, the answer may be negative, thus suggesting a change in our therapeutic strategies. In this article, we address this challenge by suggesting that it is time to develop a “treat to target strategy” for KOA.Keywords: osteoarthritis, knee osteoarthritis, treat to target